2015
DOI: 10.1093/chromsci/bmv166
|View full text |Cite
|
Sign up to set email alerts
|

Determination of γ-Aminobutyric Acid (GABA) in Rambutan Fruit cv. Rongrian by HPLC-ELSD and Separation of GABA from Rambutan Fruit Using Dowex 50W-X8 Column

Abstract: A high-performance liquid chromatography method coupled with an evaporative light scattering detector (ELSD) was validated for the determination of γ-aminobutyric acid (GABA) in rambutan fruit without any sample pretreatment or derivatization. In the concentration range of 0.05-1.0 mg/mL GABA, the ELSD response was linear with a correlation coefficient (r) >0.999. Limit of detection and limit of quantitation were found to be 0.7 and 2.0 µg/mL, respectively. The method enabled the complete separation of GABA in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…DW, while ZDZ had the lowest of 51.16 µg.g −1 .FW or 150.31 µg.g −1 .DW. The concentrations of GABA in some fruits have been reported previously, such as rambutan 710 µg.g −1 .FW (Meeploy & Deewatthanawong, 2016), strawberry 1560-3640 µg.g −1 .FW (Deewatthanawong et al, 2010), grape 146 µg.g −1 .FW (Ramesh et al, 2017), loquat 15.6-36.4 µg.g −1 .FW (Cao et al, 2012), logan 1998 µg.g −1 (Zhou et al, 2016) and litchi 1700-3500 µg.g −1 .FW (Zi- Chen et al, 2016). Compared with these fruits, jujube fruit contains a relatively low amount of GABA.…”
Section: Gaba Of Fresh Jujubesmentioning
confidence: 59%
See 2 more Smart Citations
“…DW, while ZDZ had the lowest of 51.16 µg.g −1 .FW or 150.31 µg.g −1 .DW. The concentrations of GABA in some fruits have been reported previously, such as rambutan 710 µg.g −1 .FW (Meeploy & Deewatthanawong, 2016), strawberry 1560-3640 µg.g −1 .FW (Deewatthanawong et al, 2010), grape 146 µg.g −1 .FW (Ramesh et al, 2017), loquat 15.6-36.4 µg.g −1 .FW (Cao et al, 2012), logan 1998 µg.g −1 (Zhou et al, 2016) and litchi 1700-3500 µg.g −1 .FW (Zi- Chen et al, 2016). Compared with these fruits, jujube fruit contains a relatively low amount of GABA.…”
Section: Gaba Of Fresh Jujubesmentioning
confidence: 59%
“…These functions of GABA are quite similar to those which have been described following consumption of jujube fruit. The concentrations of GABA in some fruits have been reported previously, including rambutan (Meeploy & Deewatthanawong, 2016), strawberry (Deewatthanawong, Nock, & Watkins, 2010), grape (Ramesh, Tyerman, Gilliham, & Xu, 2017), loquat (Cao, Cai, Yang, & Zheng, 2012), logan (Zhou, Ndeurumio, Zhao, & Hu, 2016) and litchi (Zi-Chen et al, 2016). However, to the best of our knowledge, no studies have been previously reported the presence of GABA in jujube.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…An SBA-40E biosensor was used to monitor the glucose and L-glutamate concentrations in the fermentation and transformation processes, respectively. The high-performance liquid phase was used to monitor the concentration of GABA before and after GAD mutation according to the method specified by Meeploy and Deewatthanawong, Wang et al [30,31].…”
Section: Methodsmentioning
confidence: 99%
“…Fast inhibitory neurotransmission in the mammalian central nervous system (CNS) is principally mediated by the ubiquitous neurotransmitter GABA (γ-aminobutyric acid) and its synaptic target, the type A GABA receptor (GABA A R). The GABA A R is a channel-forming protein that decreases the neuronal excitability by allowing the passage of chloride ions into the cells. A dysfunction in GABA A R signaling triggers various hyperactive neurological disorders and mental illnesses including Alzheimer’s disease, epilepsy, anxiety, and insomnia. The GABA A R is a prolific target in therapeutics for a diverse array of drugs, including benzodiazepines, barbiturates, anesthetics, and ethanol, that act through distinct binding sites. Variety of methods have been developed for the detection of GABA, based on in vivo magnetic resonance spectroscopy (MRS), microdialysis, electrochemical and piezoelectric methods, genetically encoded sensor, nanomaterials-based sensor etc. However, GABA A R-targeted diagnostic methods are still lacking because they have poor spatiotemporal resolution, are time consuming, and have low sensitivity. , Nonetheless, reported methods for the cellular transporting of GABAergic drugs along with cellular imaging/labeling techniques are really scarce. To this end, FONPs can serve as an emerging probe for bioimaging as well as cellular transportation of cargos.…”
Section: Introductionmentioning
confidence: 99%